Proceedings of the Workshop on Multiword Expressions Integrating Processing - MWE '04 2004
DOI: 10.3115/1613186.1613193
|View full text |Cite
|
Sign up to set email alerts
|

Representation and treatment of multiword expressions in Basque

Abstract: This paper describes the representation of Basque Multiword Lexical Units and the automatic processing of Multiword Expressions. After discussing and stating which kind of multiword expressions we consider to be processed at the current stage of the work, we present the representation schema of the corresponding lexical units in a generalpurpose lexical database. Due to its expressive power, the schema can deal not only with fixed expressions but also with morphosyntactically flexible constructions. It also al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…This method is not really adequate for processing collocations because they have a high morphosyntactic flexibility. Alegria et al [4] and Villavicencio et al [5] adopted a compositional approach to the encoding of MWEs, able to capture more morphosyntactically flexible MWEs. Alegria et al [4] showed that by using a MWE processor in the preprocessing stage, a significant improvement in the POS tagging precision is obtained.…”
Section: Multiword Expressions: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is not really adequate for processing collocations because they have a high morphosyntactic flexibility. Alegria et al [4] and Villavicencio et al [5] adopted a compositional approach to the encoding of MWEs, able to capture more morphosyntactically flexible MWEs. Alegria et al [4] showed that by using a MWE processor in the preprocessing stage, a significant improvement in the POS tagging precision is obtained.…”
Section: Multiword Expressions: Related Workmentioning
confidence: 99%
“…Alegria et al [4] and Villavicencio et al [5] adopted a compositional approach to the encoding of MWEs, able to capture more morphosyntactically flexible MWEs. Alegria et al [4] showed that by using a MWE processor in the preprocessing stage, a significant improvement in the POS tagging precision is obtained. However, as argued by many researchers [6,7], collocation identification is best performed on the basis of parsed material.…”
Section: Multiword Expressions: Related Workmentioning
confidence: 99%
“…Calzolari et al (2002) consider MWEs to include fixed or semi-fixed phrases, compounds, support verbs, idioms, phrasal verbs, collocations, etc. Alegria et al (2004) define MWEs as referring to "both semantically compositional and non-compositional combinations, and both syntactically regular and idiosyncratic phrases" including idioms, proper names, compounds, lexical and grammatical collocations, institutionalised phrases, date and number expressions. Frequency factors can also be considered in the definition of MWEs, as for Pereira et al (2004) "sequences of words that co-occur more often than expected by chance".…”
Section: What Are Mwes?mentioning
confidence: 99%
“…Research on MWE has been done on many languages, including Basque (Alegria et al, 2004), Italian (Calzolari et al, 2002), German (Trawiński, 2003;Neumann et al, 2004), Japanese (Uchiyama and Ishizaki, 2003;Tanaka and Baldwin, 2003;Baldwin and Tanaka, 2004;Fujita et al, 2004), Portuguese (Dias, 2003;Villavicencio et al, 2004a;Baptista et al, 2004), Russian (Sharoff, 2004) and Turkish (Oflazer et al, 2004). Efforts have also been made to investigate MWEs from a multilingual perspective (Calzolari et al, 2002;Villavicencio et al, 2004a), since languages differ as to what subtypes of MWEs they have, and how they are realised in other languages.…”
Section: Current Research On Mwesmentioning
confidence: 99%
“…More recent research emphasizes the integration of MWE lexical entries into existing single word lexicons and grammar systems (Villavicencio et al, 2004;Alegria et al, 2004). There is also an attempt to take advantage of regularities in morpho-syntactic properties across MWE groups, which allows encoding the behavior of the group instead of individual expressions (Villavicencio et al, 2004;Grégoire, 2007).…”
Section: Mwe Lexical Encodingmentioning
confidence: 99%